Global burden of athletic-type knee dislocation in young adults: a GBD 2021 proxy-based analysis, 1990–2021 - Alkhatatbeh, Tariq; Alkhatatbeh, Ahmad; Chen, Weidong; Fang, Hang; Liao, Yan; Cheng, Jingyang; Liang, Hao; Liang, Zhilin; Chen, Hao; Huang, Wenyan; Fang, Zijie; Zhang, Rongkai (Frontiers in Physiology, 2026)
BackgroundKnee dislocation is an uncommon but limb-threatening injury that often arises during athletic activities and can result in neurovascular compromise, multi-ligament disruption, and long-term disability. However, the Global Burden of Disease (GBD) framework does not include a specific sports-injury category, so the contribution of athletic-type mechanisms to the global burden of knee dislocation in young adults remains unclear. We, therefore, used GBD 2021 data to estimate the young-adult component of the global burden of knee dislocation from 1990 to 2021, describe long-term trends, and compare a proxy for athletic-type mechanisms with other external causes.MethodsWe performed a secondary analysis of Global Burden of Disease 2021 estimates for knee dislocation, extracting annual incidence and prevalence for adults aged 20–40 years between 1990 and 2021 by sex. A proxy for athletic-type mechanisms was defined as cases assigned to the external-cause categories “falls” and “other exposure to mechanical forces” and was compared with transport injuries and all other external causes. We calculated population age-standardized rates per 100,000 populations with 95% uncertainty intervals and summarized temporal patterns using average annual percentage change derived from log-linear regression models.ResultsAbsolute incidence counts increased for all causes (1023103→1084122; +5.96%) and the athletic proxy (577923→675111; +16.82%), increasing the proxy’s share of 20–40 incidence from 56.49% to 62.27%. Population-weighted incidence rates decreased for all causes (61.18→46.12 per 100000; −24.62%, APC −0.94%) and the proxy (34.56→28.72; −16.90%, APC −0.74%). Prevalence rates also decreased (all causes 11.20→8.59; proxy 6.12→5.08), while prevalence counts increased (all causes 187256→202052; proxy 102281→119503). In 2021, proxy rates were higher in male individuals than in female individuals (incidence 36.49 vs. 20.76; prevalence 6.06 vs. 4.08 per 100,000). Within the proxy, falls increased from 76.58% to 81.12% of incident cases.ConclusionYoung adults carry a large global burden of knee dislocation, consistent with athletic trauma. Despite increasing counts, population-weighted rates fell steadily from 1990 to 2021; male individuals remain at higher risks, and falls dominate the proxy mechanism. The proxy approach offers a reproducible way to monitor athletic-type knee dislocations where sports-injury labels are absent.